JEWS İN CYPRUS AND THEİR AİMS - Izzet Derkan (International Journal of Research Science and Management, 2016)
This article is about all nations in Cyprus from Byzantine Rule until British Crown Colony.In this stage we have studied the development of the Jews and the importance of the Jews in aviation.